PERSISTENT LEFT SUPERIOR VENA CAVA IN PATIENT WITH PAROXYSMAL ATRIOVENTRICULAR NODAL REENTRANT TACHYCARDIA - A. Kuczaj; P. J. Stryjewski; A. R. Tomasik; E. Nowalany-Kozielska; J. Nessler (Российский кардиологический журнал, 2016)
Persistent left superior vena cava (PLSVC) is a rarely occurring congenital anomaly with the incidence of 0.3% in general population. This anomaly results from the persistence of the left anterior cardinal vein. In 90% of cases blood from PLSVC flows into the coronary sinus and then to the right atrium. It may complicate the placement of central vein catheters in the jugular and subclavian veins and, as such, cardiologists should be aware of the existence of this anatomic variant. Here we describe an adult patient with persistence of the left superior vena cava identified during made echocardiography test in a 57-year-old male patient with paroxysmal atrioventricular nodal reentrant tachycardia (AVNRT) who was admitted to a cardiac ward on a regular basis for ablation procedure.